GENEOLOGI GENDER: PEMBUKTIAN LOGIS DOMINASI SPIRITUAL WANITA ATAS PRIA: Perspektif Hermeneutik Filosofis Manawa Dharmaçastra - Adnyana, Ida Bagus (Pangkaja: Jurnal Agama Hindu, 2024)
All this time the world viewed women as weak beings and sort of alienated them in a more complex struggle of life. Women have always been the object of gender degradation which until now is still common. In fact, women are equal and equal in position to women, especially in the dimension of their spriritual understanding. To be able to prove the urgency and hypothesis, the author conducts library research whose basis is qualitative research which is then descriptively interpretively elaborated. This study provides a clear picture of how women play and contribute. The role and contribution of women became the basic basis for the author to describe the position of women reviewed through the concept of Hindu religious teachings on the basis of the text, namely Manawa Dharmaçastra. The results of this study prove textually that women have a noble position in the view of Hinduism. Manawa Dharmaçastra states that where women are respected then there happiness will be achieved, but on the contrary where women experience suffering and sadness then there destruction will occur. Respect for women is certainly based on logical arguments that can be scientifically accounted for. So the author can prove that the reason women are respected as Hindus view one of them is because women have a higher spiritual level than men. The author's view is proven through various studies conducted by several researchers including Michael Argyle; Chao-Chih Liao; Intan Indah Sari and Sari Sudarmiati; Yuni Novitasari, Syamsu Yusuf, and Ilfiandra Ilfiandra; Ita Nur Itsna; and Retno Mangestuti and Rahmat Aziz. All the studies carried out prove that women have a higher level of spirituality than men, so gender geneology greatly affects the condition of human spirititulity. Keywords: Spiritual, Gender, Manawa Dharmaçastra